2016
DOI: 10.5152/npa.2015.8832
|View full text |Cite
|
Sign up to set email alerts
|

Serum Brain-derived Neurotrophic Factor Levels among Euthymic Adolescents with Bipolar Disorder Type I

Abstract: Similar to normal BDNF levels in adult patients with BD, the normal BDNF serum levels that we found in the euthymic state in adolescents and early adulthood may be related to the developmental brain stage in our study group. It may also show a common neurobiological basis of pediatric and adult BD. Further investigations evaluating BDNF levels in different mood states could help identify the role of BDNF in the underlying pathophysiology of BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It is possible that our patients were inadequate lithium responders as lithium did not recover GDS, and it is known that excellent lithium responders are associated with normal blood BDNF levels (Rybakowski 2014). In another study with euthymic adolescents with bipolar disorder, a lower BDNF level was detected in their blood after taking lithium (Cevher et al 2016). The variations in the BDNF gene promoter region affect the expression of BDNF and its role in various neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 82%
“…It is possible that our patients were inadequate lithium responders as lithium did not recover GDS, and it is known that excellent lithium responders are associated with normal blood BDNF levels (Rybakowski 2014). In another study with euthymic adolescents with bipolar disorder, a lower BDNF level was detected in their blood after taking lithium (Cevher et al 2016). The variations in the BDNF gene promoter region affect the expression of BDNF and its role in various neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 82%
“…Seventeen studies have investigated the circulating levels of BDNF in BD patients during acute episodes compared with HC, and most of them have shown decreased BDNF circulating levels in BD patients during acute episodes when compared with HC. Only Barbosa et al (2010) [ 51 ] and Poletti et al (2017) [ 52 ] showed higher BDNF circulating levels in BD patients during acute episodes, while Binici et al (2016) [ 53 ], Ameele et al (2017) [ 54 ], and Skibinska et al (2021) [ 55 ] observed no significant difference in BDNF circulating levels between acute episodes of BD patients and HC. Most studies [ 44 , 56 , 57 , 58 , 59 , 60 ] have investigated BDNF serum levels during a depressive episode, while Tramontina et al (2009) [ 40 ], Machado-Vieira et al (2007) [ 61 ], and Oliveira et al (2009) [ 59 ] have included BD patients in a manic phase; only Piccinni et al (2014) [ 60 ] have included 19 mixed state patients, while Tunca et al (2014) [ 62 ] and Yoshimura et al (2006) [ 63 ] included both manic and depressive episodes.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies included adult patients (18–65 years), while others also included adolescents [ 53 ]. Moreover, most studies recruited chronic and medicated patients, and only a few included first-onset drug-naive patients [ 44 , 45 , 57 , 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained in different studies concerning the BDNF level in adolescents with mood disorders are inconsistent. Lack of differences in the group of euthymic as well as symptomatic patients with bipolar disorder compared to the control group was detected [ 36 , 37 , 38 , 39 , 40 ]. Correlations with amygdala volume and duration of the medication were reported [ 37 , 41 ] and lack of relationship with hippocampal volume in adolescents with bipolar disorder was found [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%